Pengaruh Bimbingan Kelompok Melalui Teknik Focus Group Discussion untuk Meningkatkan Self Efficacy Siswa SMPN 17 Medan - Dinda Febriyanti Sinaga; Abdul Aziz Rusman (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Adolescence, defined as the period between the ages of 12 and 22, is a critical transition from childhood to adulthood. During this time, kids experience a variety of challenges that impact their self-efficacy, or belief in their own abilities to achieve goals or overcome obstacles. Self-efficacy is an individual's belief in their capacity to execute specific tasks, which is significantly influenced by previous problem-solving experiences. The purpose of this study is to investigate the effectiveness of group guidance services provided at SMP Negeri 17 Medan utilizing the Focus Group Discussion (FGD) technique in boosting student self-efficacy. FGD allows group members to communicate, share perspectives, and build empathy and understanding for others, all of which can enhance self-efficacy. The study was conducted quantitatively, using a one-group pretest-posttest quasi-experimental approach. The population consists of 126 eighth-grade pupils were divided into two groups: 12 experimental students and 12 control students. Data were gathered via self-efficacy questionnaires administered before and after group guidance utilizing FGD approaches. The results demonstrated that students' self-efficacy increased significantly after participating in group guidance using the FGD technique, as evidenced by the paired samples T-test and the Mann-Whitney test. The experimental group's average self-efficacy score increased when compared to the control group, demonstrating that FGD is helpful at developing students' self-confidence. This study contributes to education by proving that group guidance services utilizing FGD methodologies can effectively promote student self-efficacy, hence promoting personal and academic growth.